Features of morfogenesis of Thymus х citriodorus (Pers.) Schreb. and Thymus marschallianus Willd. explants at the second stage of clonal micropropagation in vitro - Tevfik Arzy; Yegorova Natalia (BIO Web of Conferences)
Many species of the genus Thymus are widely known as valuable essential oil and medicinal plants that have antiseptic, anti- inflammatory and analgesic properties. The use of biotechnological methods makes it possible to increase the efficiency of traditional methods of breeding and seed production. Our investigation aimed to study the influence of the different factors on the explants morphogenesis at the 2th stage of Thymus marschallianus Willd. and Thymus × citriodorus (Pers.) Schreb. clonal micropropagation. It was established that the highest morphogenetic potential was possessed by explants of T. marschallianus, whose multiplication index reached 19.9, while that of T. × citriodorus was 10.3. The optimal culture media for T. marschallianus (½MS with 0.5 mg/l naphthylacetic acid and 20 g/l glucose) and for T. × citriodorus (MS hormone free and 20 g/l sucrose) were determined. The efficiency of culturing T. × citriodorus explants in glass jars (closed with foil) was demonstrated, which allowed increasing the multiplication index up to 2.9–6.2 times compared to using test tubes or flasks as culture vessels. It was found that a longer growing cycle (70 days) in T. × citriodorus contributed to an increase the multiplication index by 3.6 times, and in T. marschallianus – by 6.2 times compared to the standard growing cycle (40 days).